2023
DOI: 10.1186/s13011-022-00509-8
|View full text |Cite
|
Sign up to set email alerts
|

Faculty, staff, and student perceptions of substance use disorder stigma in health profession training programs: a quantitative study

Abstract: Background Research indicates that stigma impacts the care provided to individuals with Substance Use Disorders (SUDs), but perceptions of SUDs in various healthcare training programs are not well known. We aimed to characterize perceptions of faculty, staff, and students about SUD stigma in professional healthcare training programs. Methods We conducted a cross-sectional survey of faculty, staff, and students employed at or enrolled in one of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Additional barriers to expanding access to substance use disorder (SUD) care include provider attitudes and training. Providers can harbor negative sentiments about their patients with SUD, which can affect their willingness to prescribe them FDA-approved medications [ 9 , 16 , 33 ]. Discomfort in working with patients with SUD is also frequently cited, mainly due to lack of training and/or exposure to individuals with SUD [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional barriers to expanding access to substance use disorder (SUD) care include provider attitudes and training. Providers can harbor negative sentiments about their patients with SUD, which can affect their willingness to prescribe them FDA-approved medications [ 9 , 16 , 33 ]. Discomfort in working with patients with SUD is also frequently cited, mainly due to lack of training and/or exposure to individuals with SUD [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a concurrent mixed-methods study among students enrolled in six health-related colleges at one mid-south health science center in the US, including medicine, pharmacy, dentistry, nursing, health professions, and graduate health sciences [ 13 , 14 ]. Data collection of the quantitative and qualitative parts occurred at the same time over three months in 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The survey responses were also captured and stored electronically. More information about the survey development and recruitment can be found in the previously published manuscript [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, bias against patients with SUDs exist from both students and practicing physicians. Studies have shown that physicians with stigmatizing attitudes are less likely to prescribe medications to treat SUD, despite the strong evidence for their efficacy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%